Lag-length effect on repetition priming of famous and unfamiliar faces: evidence from N250r and N400. Issue 10 (6th July 2016) - Nie, Aiqing; Li, Minye; Ye, Jingheng
Abstract : Previous event-related potentials research has reliably identified two repetition priming components in faces, the N250r and the N400, which are believed to reflect, respectively, the accessing to the stored structural representations and the semantic retrieval. However, the effect of lags longer than immediate repetition and shorter than 3 min on the two components has not been described as yet, and the interaction between lag length and familiarity is unclear. The current experiment aims to address these issues. In this experiment, famous and unfamiliar faces were represented after short, medium, or long lags, and participants were required to decide whether each face was known or not. The data showed that the frontal N250r, rather than the temporal counterpart, persisted to the medium lag case for famous faces; for unfamiliar faces, no N250r was observed. The frontal N400 was more regulated by lag length than the centroparietal counterpart. These results suggest that the frontal N250r and the frontal N400 are affected by the lag length; moreover, the former is more sensitive to the pre-experimental familiarity of faces. Abstract : Supplemental Digital Content is available in the text.